1999
DOI: 10.2307/3870843
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Structural P Proteins in the Phloem

Abstract: Phloem-specific proteins (P proteins) are particularly useful markers to investigate long-distance trafficking of macromolecules in plants. In this study, genus-specific molecular probes were used in combination with intergeneric grafts to reveal the presence of a pool of translocatable P protein subunits. Immunoblot analyses demonstrated that Cucurbita spp P proteins PP1 and PP2 are translocated from Cucurbita maxima stocks and accumulate in Cucumis sativus scions. Cucurbita maxima or Cucurbita ficifolia PP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
102
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(108 citation statements)
references
References 10 publications
5
102
0
1
Order By: Relevance
“…They were first identified as components of the socalled P-proteins in cucurbits and shown to act as dimeric chitin-binding lectins in these plants (Beyenbach et al, 1974;Sabnis and Hart, 1978;Allen, 1979;Read and Northcote, 1983a;Smith et al, 1987;Bostwick et al, 1992), leading to the suggestion of a role in defense mechanisms. In C. maxima, CbmPP2 presents several properties associated with NCAPs (Bostwick et al, 1994;Balachandran et al, 1997;Golecki et al, 1998Golecki et al, , 1999, suggesting a role in the trafficking of macromolecules. However, it remains unclear whether PP2s from species other than cucurbits present such properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They were first identified as components of the socalled P-proteins in cucurbits and shown to act as dimeric chitin-binding lectins in these plants (Beyenbach et al, 1974;Sabnis and Hart, 1978;Allen, 1979;Read and Northcote, 1983a;Smith et al, 1987;Bostwick et al, 1992), leading to the suggestion of a role in defense mechanisms. In C. maxima, CbmPP2 presents several properties associated with NCAPs (Bostwick et al, 1994;Balachandran et al, 1997;Golecki et al, 1998Golecki et al, , 1999, suggesting a role in the trafficking of macromolecules. However, it remains unclear whether PP2s from species other than cucurbits present such properties.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, PP2-A1 may not be mobile in sieve elements, instead remaining bound to structural elements (Oparka and Cruz, 2000). Indeed, in C. maxima, it has been suggested that the phloem lectin attaches the P-proteins to the sieve element reticulum or plasma membrane (Smith et al, 1987), although there is also evidence to suggest that a fraction is translocated over long distances through graft unions (Golecki et al, 1998(Golecki et al, , 1999. We also cannot rule out the possibility that the method used to collect phloem sap, involving the use of EDTA, a chelator of Ca 2+ ions, affects the aggregation and mobility of PP2 proteins.…”
Section: Survey Of Phloem Sap Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…This filament protein was immunolocalized in sieve element slime plugs and P-protein bodies, whereas the corresponding mRNA was shown to accumulate in companion cells (19). PP1 also was shown to be translocated within the extraordinary extrafascicular phloem system of Cucurbitaceae (20). However, the fact that PP1 is potentially unique to cucurbit species (21), whereas the typical P-protein structures in fascicular sieve elements are morphologically comparable in all dicotyledonous angiosperms, is still a matter of debate.…”
mentioning
confidence: 93%
“…a cell-autonomous RNA specifically expressed in companion cells, 30 to test the specificity of RNA movement in our cleftgrafting experiments. The full-length cDNA of GAI and AtPP2A1 were driven by a CaMV35S promoter and introduced into Arabidopsis Columbia ecotype (Col, all transformants are in a Col background).…”
Section: Introductionmentioning
confidence: 99%